Sarmatian Elites of the Lower Volga-and-Don Region and their Relations with the Outside World (3rd c. BC – 3rd c. AD) - Mordvintseva, Valentina I. (Anabasis. Studia Classica et Orientalia, 2019)
This paper is devoted to a comparative analysis of the elite burial complexes of the Lower Volga-Don region in different periods of the Sarmatian era, and to interpretation of the changes occurring in their distribution and composition. An overview of the changes in the rite, composition of burial goods, and spatial distribution of the “Barbarian” elite graves of the Volga-Don region demonstrates the social structure of nomadic societies becoming more complex over time and becoming orientated towards the settled centers of the Northern Black Sea region, especially to the city of Tanais. An additional source of information is the composition and origin of the “prestige items” found in these graves. According to their analysis, cultural groups with different thanatological doctrines, in other words culturally varying societies, participated in the process. It seems that the observed changes were largely not due to the “regular migratory waves of nomads from East to West,” but to foreign political factors, in particular the development of relations between the major political powers of the era – Parthia and Rome. An important strategic role in their struggle was played by the Caucasus and the countries adjacent to it to the north, where the Bosporan Kingdom occupied a pivotal position: Its Asian part directly bordered numerous warlike “Barbarian” tribes of the North Caucasus and the Eastern Azov areas. Steppe peoples of the North Caucasus exerted a strong influence on the political affairs in southern Caucasia, including Iberia, Albania, Armenia, and in Media Atropatene and Parthia as well. The nomadic chiefdoms of the Volga-Don region, with their significant military potential, were obviously involved in internal and foreign political conflicts in the territories of the Bosporan Kingdom and the Caucasus. Evidently, the booty and gifts obtained in the course of military actions and conclusions of treaties and agreements were partially demonstrated in the funeral ceremonies of the “Barbarian” nobility, reinforcing their claims to leadership. These artifacts, discovered at necropolises in burial complexes, show different aspects of the culture and policies which involved the Sarmatian elites.